PERBUDAKAN MODERN DI ARAB SAUDI: SEKSUALITAS MAJIKAN DAN BUDAK PEREMPUAN DI ZAMAN JAHILIYAH - La maa, Fini; Mutalib, Abdul; Nasim, Abu Sahman (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2024)
Slavery is not a product of Islam as it existed long before the Prophet Muhammad came. Even in the Qur'an, there are strong indications that enjoying sex with an unmarried slave girl is the same as enjoying it with a legal wife, so it is not even called zina in the Qur'an. It is evident that during the pre-Islamic era, sexuality between a master and his slave girl was commonplace. This research is a literature that is sourced in the form of books, journals and previous research that has the same theme of discussion as this issue. The result of this writing is that in Islam, the master or employer having sex with a slave girl is allowed and is not called adultery because it is stated in the Al-Qur'an surah Al-Mu'minun verses 5-7. The slavery that currently occurs in Saudi Arabia with various forms of slavery, one of which is the forced sexual intercourse of the master against his slave girl, is an act that is strictly prohibited and hated in Islam because it lowers the dignity and dignity of women.